Buckling Analysis of Spherical Composite Panels Reinforced by Carbon Nanotube - Saleh Pouresmaeeli; S. Ahmad Fazelzadeh; Esmaeal Ghavanloo (Mechanics of Advanced Composite Structures)
In this study, the buckling behavior of moderately thick Carbon Nano-Tube (CNT)-reinforced spherical composite panels subjected to both uniaxial and biaxial loads is examined. The uniform and various kinds of functionally graded distributions of the CNT are considered. The mechanical properties of the nanocomposite panels are estimated using the modified rule of mixture. Based on the first-order shear deformation theory and the von Karman-type of kinematic nonlinearity, the governing differential equations are derived and the solutions are determined using Galerkin’s method. The suggested model is justified by a good agreement between the present results and those reportedin the literature. The numerical results are performed to elucidate the influences of volume fraction, aspect ratio, thickness ratio and side-to-radius ratio on the critical buckling loads of the spherical nanocomposite panels. One of the main contributions of the current study is to investigate the effectiveness of functionally graded distributions.The effectiveness of functionally graded distributions with respect to various parameters are also investigated.